Teaching Speaking at Upper Secondary Schools to Achieve Communicative Competence - Rawsthorne, Daniela (Univerzita Pardubice, 2012)
This thesis discusses teaching speaking at upper-secondary schools towards achieving communicative competence. The theoretical part outlines the concept of communicative competence as reflected in speaking, as well as basic principles of syllabus design. Testing speaking is discussed, together with a critical analysis of the reformed final examination. The main outcome of the practical part is the development of teaching and testing materials, reflecting the theoretical background.
Výuka mluveného projevu na střední škole pro dosažení komunikativní kompetence
Keywords: komunikativní kompetence; mluvený projev; výuka a testování mluveného projevu; tvorba sylabu; communicative competence; speaking; teaching speaking; testing speaking; syllabus design